Upaya Peningkatan Motivasi Belajar Eksternal dalam Model Pembelajaran Kontekstual di SMP Brawijaya Smart School - Azzahra, Aulivia Harindi Nur; Wildana, Amran Roky; Aulia, Kayla Wahyu; Abadi, Machrus (Medan Resource Center, 2024)
Learning motivation is a state in which an individual exhibits a desire to achieve learning objectives. This study aims to explore the application of contextual teaching models in fostering student motivation, identify strategies used to motivate students, and analyze efforts to enhance learning motivation. This research employs a qualitative descriptive method with a mixed approach, emphasizing the natural environment as its context. Data collection involved interviews with Mrs. Dini and 7B class students to gather qualitative insights. Findings reveal that educators and schools play a crucial role in enhancing both internal and external motivation. Efforts such as creating supportive environments for extracurricular activities, accommodating active student assessments, and providing intensive guidance significantly contribute to student commitment toward their personal development. Strong learning motivation, whether derived from internal or external sources, positively influences academic performance and prepares students to tackle real-world challenges effectively. These results emphasize the need for a holistic approach in integrating motivational strategies within educational frameworks.